2014
DOI: 10.2337/db13-1483
|View full text |Cite|
|
Sign up to set email alerts
|

Body Fat Partitioning Does Not Explain the Interethnic Variation in Insulin Sensitivity Among Asian Ethnicity: The Singapore Adults Metabolism Study

Abstract: We previously showed that ethnicity modifies the association between adiposity and insulin resistance. We sought to determine whether differential body fat partitioning or abnormalities in muscle insulin signaling associated with higher levels of adiposity might underlie this observation. We measured the insulin sensitivity index (ISI), percentage of body fat (%body fat), visceral (VAT) and subcutaneous (SAT) adipose tissue, liver fat, and intramyocellular lipids (IMCL) in 101 Chinese, 82 Malays, and 81 South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 22 publications
4
46
0
Order By: Relevance
“…32,33 Although the relationship between IMCL and metabolic function may depend on the training status of the subjects, 34 the correlations of IMCL with insulin sensitivity and insulin secretion in our study remained not significant even after adjusting for VO 2 max (r = −0.191, P = 0.152 and r = 0.208, P = 0.117; respectively). As our subjects were of Asian descent (predominantly Chinese), our findings are consistent with the results of Khoo et al 35 who reported weak associations between IMCL content and insulin sensitivity in all Asian ethnic groups, along with a reduced tendency for Chinese subjects to accumulate IMCL with increasing levels of adiposity. In addition, there are differences in IMCL content between different muscles, 36 thus we cannot rule out the possibility that the soleus is not a representative skeletal muscle with respect to the relationship between IMCL and whole-body insulin sensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…32,33 Although the relationship between IMCL and metabolic function may depend on the training status of the subjects, 34 the correlations of IMCL with insulin sensitivity and insulin secretion in our study remained not significant even after adjusting for VO 2 max (r = −0.191, P = 0.152 and r = 0.208, P = 0.117; respectively). As our subjects were of Asian descent (predominantly Chinese), our findings are consistent with the results of Khoo et al 35 who reported weak associations between IMCL content and insulin sensitivity in all Asian ethnic groups, along with a reduced tendency for Chinese subjects to accumulate IMCL with increasing levels of adiposity. In addition, there are differences in IMCL content between different muscles, 36 thus we cannot rule out the possibility that the soleus is not a representative skeletal muscle with respect to the relationship between IMCL and whole-body insulin sensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, previous comparisons of racial/ethnic groups have noted that even after adjustment for visceral, subcutaneous, and hepatic density, Asian Indians have lower insulin sensitivity using hyperinsulinemic euglycemic clamp studies compared with other Asian groups. 24 In turn, insulin sensitivity is a known modifier of lipid particle size and activity, with greater insulin resistance contributing to lower HDL levels. 25 Thus, relationships between sex hormones and HDL may have been attenuated in the current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Sex and ethnic differences in abdominal fat partitioning have been reported in adolescents and adults (11)(12)(13)(14)(15), with multiple studies showing that men have higher levels of VAT than women, which may partly explain their increased predisposition to metabolic diseases (11,12,16). The timing of this sexual dimorphism is not clear, with some reports indicating that it emerges even before puberty (17).…”
Section: Introductionmentioning
confidence: 99%